2014
DOI: 10.4028/www.scientific.net/amm.695.155
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Hybrid Sugar Palm/Kenaf Fibre Reinforced Polypropylene Composites

Abstract: Study on hybridization of two types of natural fibres reinforced thermoplastic composites was an alternative option in research on natural composites. This paper presents the investigation on tensile properties of combining sugar palm and kenaf fibres reinforced polypropylene composites. The hybrid composites were prepared with different amounts of fibres (i.e. 10%, 20% and 30% by weight percent) while the ratios between sugar palm and kenaf fibre are 30:70, 50:50 and 70:30. The composites have been fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Besides, 40UTK and 50UTK samples, fiber pulled-out, and broken fiber were the cause of fracture (Figure 3(c) and 3(d)). Yet, the 50UTK sample has better fiber/resin interface which leads to the good load transfer mechanism [24]. On the opposite, for the 60UTK sample (Figure 3(e)), the excess amount of fiber compared with the amount of cardanol leads to poor interfacial bonding, due to lack of resin.…”
Section: Morphology Study Of the Compositesmentioning
confidence: 96%
“…Besides, 40UTK and 50UTK samples, fiber pulled-out, and broken fiber were the cause of fracture (Figure 3(c) and 3(d)). Yet, the 50UTK sample has better fiber/resin interface which leads to the good load transfer mechanism [24]. On the opposite, for the 60UTK sample (Figure 3(e)), the excess amount of fiber compared with the amount of cardanol leads to poor interfacial bonding, due to lack of resin.…”
Section: Morphology Study Of the Compositesmentioning
confidence: 96%
“…One of the main reasons is probably the weak interaction between both fibers and the fibers-matrix interface, affecting the tensile strength of the composites because of the polarity differences of the PP polymer matrix and natural fibers. 37,42 However, the tensile strength of the hybrid composites was still acceptable as it was recorded to achieve beyond 15 MPa for each of the ratio compositions.…”
Section: Tensile Propertiesmentioning
confidence: 97%
“…In conclusion, they suggested that a hybrid composite with a greater volume of KFs has better properties than a hybrid containing more SPFs. 37…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another research study observed hybrid composites with different composition that were prepared with different amounts of fibers (i.e., 10%, 20% and 30% by weight percent), in which the ratios between sugar palm and kenaf fiber were 30:70, 50:50, and 70:30. The study found that the tensile strength of composites tended to decrease when the content of loading fibers increased [ 30 ]. Therefore, the current study focused only on the implementation of 10% of kenaf/sugar palm as the composite filler content in order to offer better bonding between the fibers and polypropylene matrix.…”
Section: Introductionmentioning
confidence: 99%